Dynamics of the In vitro Growing of Mycobacterium bovis from the Lungs of Vaccinated and Infected Mice - Federico Carlos Blanco; Laura Inés Klepp; Cristina Lourdes Vazquez; Fabiana Bigi (International Journal of Mycobacteriology)
Background: Bovine tuberculosis (bTB) is a disease primarily caused by Mycobacterium bovis. Currently, no commercial vaccines exist for controlling bTB, making the development of effective vaccine candidates and testing models a high priority. Mouse models are widely used in preclinical trials of anti-TB vaccines. Determining the appropriate cultivation time to assess the mycobacterial load in animal organs or biological samples is crucial to establishing a reliable model that can accurately evaluate the effectiveness of a vaccine candidate. The aim of this study was to assess the growth dynamics and the appearance of colony-forming units (CFUs) in lung homogenates from mice infected with M. bovis. We compared the CFU counts from vaccinated and challenged mice with M. bovis using data from a previous experiment. Methods: CFUs obtained from the lungs of vaccinated and M. bovis-challenged mice of a previous experiment were registered at 3 and 4 weeks of culturing in solid media. The statistical analysis was performed with Kruskal–Wallis, followed by a Dunn’s multiple comparison test. Results: On analyzing the CFU dynamics from lung homogenates, we found that mice vaccinated with Bacillus Calmette–Guérin preserved stable CFU counts after 3 weeks of cultivation on a solid medium. In contrast, both the unvaccinated group and the group vaccinated with an attenuated M. bovis triple mutant strain reached their final CFU counts only after 4 weeks of culturing. Conclusion: These findings underscore the importance of prolonged follow-up to accurately assess CFU counts, which are crucial for determining vaccine efficacy in trials.